In situ Electrochemical Studies of the Terrestrial Deep Subsurface Biosphere at the Sanford Underground Research Facility, South Dakota, USA - Jangir, Yamini; Karbelkar, Amruta A.; Beedle, Nicole M.; Zinke, Laura A.; Wanger, Greg; Anderson, Cynthia M.; Reese, Brandi Kiel; Amend, Jan P.; El-Naggar, Mohamed Y. (Frontiers in Energy Research, 2019)
The terrestrial deep subsurface is host to significant and diverse microbial populations. However, these microbial populations remain poorly characterized, partially due to the inherent difficulty of sampling, in situ studies, and isolating of the in situ microbes. Motivated by the ability of microbes to gain energy from redox reactions at mineral interfaces, we here present in situ electrochemical colonization (ISEC) reactor as a method to directly study microbial electron transfer activity and to enable the capture and isolation of electrochemically active microbes. We installed a potentiostatically controlled ISEC reactor containing four working electrodes 1,500 m below the surface at the Sanford Underground Research Facility (SURF). The working electrodes were poised at different redox potentials to mimic energy-yielding mineral reducing and oxidizing reactions predicted to occur at this site. We present a 16S rRNA analysis of the in situ electrode-associated microbial communities, revealing the dominance of novel bacterial lineages under cathodic conditions. We also demonstrate that the in situ electrodes can be further used for downstream electrochemical laboratory enrichment and isolation of novel strains. Using this workflow, we isolated Bacillus, Anaerospora, Comamonas, Cupriavidus, and Azonexus strains from the electrode-attached biomass. Finally, the extracellular electron transfer (EET) activity of Comamonas strain (isolated at −0.19 V vs. SHE and designated WE1-1D1) and Bacillus strain (isolated at +0.53 V vs. SHE and designated WE4-1A1-BC) from and to a poised electrode, respectively, were confirmed in electrochemical reactors. Our study highlights the utility of in situ electrodes and electrochemical enrichment workflows to shed light on microbial activity in the deep terrestrial subsurface.